2022
DOI: 10.1177/19312431221095207
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Human Too”: Media Coverage of Simone Biles's Mental Health Disclosure during the 2020 Tokyo Olympics

Abstract: When gymnast Simone Biles withdrew from several events at the 2020 Tokyo Olympics due to concern for her mental health, media organizations discussed both her departure and return to competition. Utilizing framing theory, 192 domestic and international news sources published from July to August 2021 were thematically analyzed to examine how media covered Biles's exit and ultimate return to competition. Results show media covered Biles overwhelmingly positively while focusing on her mental health, productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Entman's discussion of framing involves valence such as positive or negative and includes the selection or emphasis of concepts in text (Entman, 1993). We drew upon the themes identified by Thompson et al's (2022) study of Simone Biles, which also followed Entman's tenants of framing but rely on Thompson's work because the frames identified were appropriate for the context of the present study and in a sport context. These themes included mental health disclosure, symptoms, implications for individuals and teams, heroism, courage, bravery, and self-care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entman's discussion of framing involves valence such as positive or negative and includes the selection or emphasis of concepts in text (Entman, 1993). We drew upon the themes identified by Thompson et al's (2022) study of Simone Biles, which also followed Entman's tenants of framing but rely on Thompson's work because the frames identified were appropriate for the context of the present study and in a sport context. These themes included mental health disclosure, symptoms, implications for individuals and teams, heroism, courage, bravery, and self-care.…”
Section: Methodsmentioning
confidence: 99%
“…Parrott and colleagues (2021) identified a prevalent portrayal in traditional media of athletes as “invincible.” This might be attributed to societal ideals regarding masculinity, potentially rendering any counter-narrative more challenging for audiences to engage with. Thompson et al (2022) found that media coverage of Simone Biles during the Tokyo 2020 Olympic Games was overwhelmingly positive and further noted that “hero” narratives were found in much of that coverage. According to Parrott et al (2021), media frames regarding NBA star Kevin Love’s struggles with mental health were typically positive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We chose the article published first for consistency, and also due to it being the closest chronologically to the news breaking about the athlete's mental ill health. While we are aware that factors such as the athlete's gender and ethnicity may be influential in the framing of media reporting (Thompson et al, 2022), we did not include this layer of complexity in our study. We do acknowledge that an intersectional approach to this area of study may be beneficial, however, we felt it beyond the scope of the aims of the current study.…”
Section: Samplementioning
confidence: 99%
“…DeRozan have spoken about their mental health and these disclosures have given rise to a growing body of research on the media framing of mental illness (e.g., Cassilo, 2022;Cassilo, & Kluch, 2023;Lavelle, 2021;Parrott et al, 2020;Parrott et al, 2021;Thompson et al, 2022). Parrott et al (2021) found that news stories of Love and DeRozan framed the athletes as strong characters for disclosing mental health battles in a sport culture that frequently stigmatises any potential weaknesses.…”
mentioning
confidence: 99%
See 1 more Smart Citation